A highly efficient polyampholyte hydrogel sorbent based fixed-bed process for heavy metal removal in actual industrial effluent. (1st February 2016) - Zhou, Guiyin; Luo, Jinming; Liu, Chengbin; Chu, Lin; Ma, Jianhong; Tang, Yanhong; Zeng, Zebing; Luo, Shenglian
Abstract: High sorption capacity, high sorption rate, and fast separation and regeneration for qualified sorbents used in removing heavy metals from wastewater are urgently needed. In this study, a polyampholyte hydrogel was well designed and prepared via a simple radical polymerization procedure. Due to the remarkable mechanical strength, the three-dimensional polyampholyte hydrogel could be fast separated, easily regenerated and highly reused. The sorption capacities were as high as 216.1 mg/g for Pb(II) and 153.8 mg/g for Cd(II) owing to the existence of the large number of active groups. The adsorption could be conducted in a wide pH range of 3–6 and the equilibrium fast reached in 30 min due to its excellent water penetration for highly accessible to metal ions. The fixed-bed column sorption results indicated that the polyampholyte hydrogel was particularly effective in removing Pb(II) and Cd(II) from actual industrial effluent to meet the regulatory requirements. The treatment volumes of actual smelting effluent using one fixed bed column were as high as 684 bed volumes (BV) (7736 mL) for Pb(II) and 200 BV (2262 mL) for Cd(II). Furthermore, the treatment volumes of actual smelting effluent using tandem three columns reached 924 BV (31, 351 mL) for Pb(II) and 250 BV (8483 mL) for Cd(II), producing only 4 BV (136 mL) eluent. Compared with the traditional high density slurry (HDS) process with large amount of sludge, the proposed process would be expected to produce only a small amount of sludge. When the treatment volume was controlled below 209.3 BV (7103 mL), all metal ions in the actual industrial effluent could be effectively removed (<0.01 mg/L). This wok develops a highly practical process based on polyampholyte hydrogel sorbents for the removal of heavy metal ions from practical wastewater. Graphical abstract: Highlights: Excellent mechanical strength for separation and reusability. Fast sorption rate and high sorption capacity. High treatment capacity on fixed-bed column. Efficient removal of toxic metal ions from industrial effluent.